Impact of Fabrication Processes of Small-Molecule-Doped Polymer Thin-Films on Room-Temperature Phosphorescence - Thomas, Heidi; Haase, Katherina; Achenbach, Tim; Bärschneider, Toni; Kirch, Anton; Talnack, Felix; Mannsfeld, Stefan C. B.; Reineke, Sebastian (Frontiers in Physics, 2022)
The development of organic materials displaying room-temperature phosphorescence is a research field that has attracted more and more attention in the last years. Most studies focus on designing or optimizing emitter molecules to increase the phosphorescent performance in host:emitter systems. Rarely, the overall thin-film preparation routines are compared with respect to their triplet-state luminescence yield. Herein, different film preparation techniques are investigated using the very same emitter molecule. A variation of host polymer, post-annealing temperature, and fabrication procedure is evaluated with respect to the obtained phosphorescent lifetime, photoluminescent quantum yield, and phosphorescence-to-luminescence ratio. This study elaborates the importance of different film preparation techniques and gathers a concise set of data which is helpful to anyone optimizing the phosphorescence of a particular system.